2021
DOI: 10.3332/ecancer.2021.1226
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-oncology service provisions for hospitalised cancer patients before and during the COVID-19 pandemic in an oncology centre in eastern India

Abstract: Background: Addressing the mental health needs of cancer patients and their caregivers improves the quality of care the patient receives in any cancer care ecosystem. International practice currently encourages integrated care for physical and mental health in oncology. The coronavirus disease (COVID-19) pandemic has affected the delivery of healthcare services across the world. The current research paper is on the psycho-oncology service provision for hospitalised cancer patients before and during the COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…"The SARS-CoV-2 pandemic had affected cancer care and service delivery around the world and we published the impact of the pandemic on psycho-oncology services separately." 21 A recent review 22 covering several studies around the globe, including India, concluded the prevalence of depression in breast cancer to be around 32%. The higher rates of psychiatric morbidity reported in this audit were perhaps because we only evaluated patients who were referred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"The SARS-CoV-2 pandemic had affected cancer care and service delivery around the world and we published the impact of the pandemic on psycho-oncology services separately." 21 A recent review 22 covering several studies around the globe, including India, concluded the prevalence of depression in breast cancer to be around 32%. The higher rates of psychiatric morbidity reported in this audit were perhaps because we only evaluated patients who were referred.…”
Section: Discussionmentioning
confidence: 99%
“…19 The role of psychosocial support remains crucial in treatment. “The SARS-CoV-2 pandemic had affected cancer care and service delivery around the world and we published the impact of the pandemic on psycho-oncology services separately.” 21…”
Section: Discussionmentioning
confidence: 99%
“…The timing of participant recruitment, before or after COVID‐19 pandemic, influenced the study findings. Pre‐COVID participants would provide insights based on traditional, face‐to‐face healthcare experiences, touching on aspects like wait times, doctor–patient interactions and the comfort of healthcare facilities (Mukherjee et al., 2021). Post‐COVID participants, having experienced the shift to telehealth, discussed the challenges and advantages of this new model, such as navigating virtual services, the emotional impact of reduced personal contact, and benefits like increased accessibility and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it provides another approach to support and consolidate psychologically supportive consulted physical therapy, such as palliative care via telehealth in accommodating cancer survivors' need for physical activity, health and nutrition, and support in coping with insomnia, tiredness and fatigue and stress related toCOVID-19 pandemic (El Keshky et al, 2020;Hazin & Qaddoumi, 2010;Helm et al, 2020).The timing of participant recruitment, before or after COVID-19 pandemic, influenced the study findings. Pre-COVID participants would provide insights based on traditional, face-to-face healthcare experiences, touching on aspects like wait times, doctor-patient interactions and the comfort of healthcare facilities(Mukherjee et al, 2021). Post-COVID participants, having experienced the shift to telehealth, discussed the challenges and advantages of this new model, such as navigating virtual services, the emotional impact of reduced personal contact, and benefits like increased accessibility and safety.…”
mentioning
confidence: 99%